Геоэкологические проблемы и социально-экономические перспективы освоения Азовского побережья - Богун, Л.Д.; Таранец, В.И.; Заборин, М.С.; Хромов, А.Н. (Український науково-дослідницький і проектно-конструкторський інститут гірничої геології, геомеханіки і маркшейдерської справи НАН України, 2009)
The paper touches upon geoecological problems of the Azov Sea coast, prospects for development of social sphere and also necessary measures are proposed that provide normal building and use of constructions located along the Azov Sea coast.